A study on the correlation between job training and job performance among working students - Antido, Jowella L., Baldove, Riezl Annd M., Belizon, Ahrabella Kelly, Corbito, Khyle Justine P., Gatbonton, Lian Ysabelle T., Gatmaitan, Jasmine Reigne P., Jistre, Ma. Allysa E. 4 0 16; 5
Abstract This study investigates the intricate relationship between job training and the job performance of working students at Pamantasan ng Lungsod ng Maynila, focusing on the Marketing and Economics programs. The researchers conducted a descriptive-explanatory survey of 130 working students during the first semester of the 2023-2024 academic year. Respondents from Business Economics and Marketing Management programs used a Likert Scale to express their perceptions of training program quality and its impact on job performance. Data analysis involved the application of statistical methods, encompassing both Spearman's rank-order correlation (Spearman's rho) and analysis of variance (ANOVA). The study found a significant difference in job performance levels among students who received varying qualities of job training. The research concludes that students receiving adequate job training are likelier to exhibit commitment, produce high-quality work, undergo positive behavioral changes, and establish effective working styles. These results align with Kirkpatrick's Model of Four-Level Training Evaluation, indicating a positive return on investment for organizations investing in job training. The comparative analysis findings revealed a significant positive correlation between job training and job performance, suggesting that higher-quality training is linked to improved job performance. The research study aims to provide insights into job training and performance dynamics among working students, offering a basis for institutions to optimize programs and cultivate a conducive working environment for this unique demographic.
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2